Catching-up and falling behind: Effects of learning in an R&D differential game with spillovers - Anton Bondarev; Alfred Greiner (University of Basel, Center of Business and Economics (WWZ), 2017)
In this paper we analyze the dynamics of an R&D differential game allowing for technological spillovers and sigmoid learning functions of multiproduct oligopolies. We demonstrate how the presence of learning together with spillovers may generate a rich set of outcomes, varying from constant leadership to catching-up and falling behind as well as from technology lock-in to a situation with a large number of high quality products. These types of outcomes are qualitatively different both from the single firm dynamics with learning and from the duopoly case with spillovers and without learning.
Keywords: C61; C73; L13; L16; O32; O33; 330; endogenous market structure; learning by doing; technological spillovers; heterogeneous innovations; differential games